Essential oils from Acronychia pedunculata (L.) Miq. in Vietnam: chemical composition, antimicrobial, cytotoxicity and nitric oxide inhibition activities - Trịnh, Thị Điệp (Taylor & Francis, 2024)
The chemical composition, antimicrobial, cytotoxic and anti-inflammatory activities of essential oils from different parts of Acronychia pedunculata, a medicinal plant native to Central Highlands of Vietnam, were investigated. Their chemical constituents were determined using GC-MS. The antimicrobial properties were assessed using a microdilution broth method, while the anti-inflammatory properties were measured based on their capacity to inhibit NO production in macrophage cells. Their cytotoxicity was tested using the sulforhodamine B assay on three human cancer cell lines. The GC-MS analysis revealed the presence mainly of caryophyllene oxide (35.3%) and spathulenol (31.9%) in the stem essential oil, caryophyllene oxide (51.3%), and linalool (21.0%) in the leaf essential oil, and α-pinene (21.4%), (E)-β-ocimene (16.5%), linalool (12.5%), and β-caryophyllene (13.0%) in the fruit essential oil. All three essential oils inhibited the growth of various bacteria and fungi, reduced NO production in LPS-induced RAW264.7 cells, and exhibited cytotoxicity against all three tested cancer cell lines. Notably, the fruit essential oil showed the most potent cytotoxicity among the essential oils, with IC50 values of 5.47 ± 0.21, 7.95 ± 0.35, and 9.22 ± 0.52 g/mL against SK-LU-1, MCF-7, and HepG2 cells, respectively. It also had a strong anti-inflammatory effect that was comparable to that of dexamethasone, with an IC50 value of NO production inhibition of 14.62 ± 0.62 mg/mL. These results suggest the potential of the essential oils from this plant to provide leads for the development of anti-inflammatory and anti-cancer agents.